Effect of Dimilin and Deltamethrin on development of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Tribolium castaneum; dimilin; deltamethrin; development Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 87-91